Business model options for the university of the future in the era of IR4.0: humanising entrepreneurship education for the Sudanese youths - Abdalgader Guma, Abdalhamid; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
Youths represents the future of each country. Building strategies that can helps to enhance the societal well-being and reduce the unemployment rate in any society must involve youth. Entrepreneurship plays an important role in building a harmonious and caring society including enhancing the economic growth and jobs creation. This paper offers business model options for a Malaysian University of the Future (UotF) with the value proposition of humanising entrepreneurship education in nurturing balanced graduates students who have the knowledge, skills and human values. This paper adopted the design thinking and system thinking approach involving conducting literature review and interviews in understanding youth unemployment issues in Sudan; analysing, formulating and validation of conceptual solution options using business modelling tools such as BMC and VPCs. The initial BMC and VPC are formulated by conducting a literature review and interviews to identify the key issues and develop possible business model options. These business models have been validated by interviewing the officers of the Malaysian UotF and customer segments. The key contributions of the paper – a conceptual business model of the Malaysian UotF; conceptual community engagement programmes in Sudan in enhancing the societal well-being and enhancing job opportunities through humanising entrepreneurship education; other universities can adapt the business model in meeting their needs.